2017
DOI: 10.1038/nclimate3276
|View full text |Cite
|
Sign up to set email alerts
|

Biochar built soil carbon over a decade by stabilizing rhizodeposits

Abstract: Biochar can increase the stable C content of soil. However, studies on the longer-term role of plant-soil-biochar interactions and the consequent changes to native soil organic carbon (SOC) are lacking. Periodic 13 CO 2 pulse labelling of ryegrass was used to monitor belowground C allocation, SOC priming, and stabilization of root-derived C for a 15-month period-commencing 8.2 years after biochar (Eucalyptus saligna, 550 • C) was amended into a subtropical ferralsol. We found that field-aged biochar enhanced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
94
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 281 publications
(101 citation statements)
references
References 56 publications
6
94
0
1
Order By: Relevance
“…reduced SOM decomposition and lower CO 2 effluxes), this period could be quite long. For our case, in which a positive priming was observed, which is consistent with expectations for a sandy soil 14 , the minimum period of climatic benefit could be less.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…reduced SOM decomposition and lower CO 2 effluxes), this period could be quite long. For our case, in which a positive priming was observed, which is consistent with expectations for a sandy soil 14 , the minimum period of climatic benefit could be less.…”
Section: Discussionsupporting
confidence: 91%
“…Further, our study did not consider the enhanced biomass growth commonly observed in response to biochar additions to forest soils 7 . In particular, it has been shown that biochar can stabilize root-derived carbon 14 , and even when biochar causes a short-term positive priming of native SOM, the biochar remains stable in soils over centuries 16 to millennial time scales 29 with a net positive impact on soil C stocks 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous isotopic tracer studies have shown a strong coupling between recently fixed plant photosynthates and belowground C allocation to roots, soil microbes and respiratory fluxes (Bahn et al, 2013;Barthel et al, 2014;Epron et al, 2011;Hogberg et al, 2008;Jin and Evans, 2010;Sommer et al, 2016;Street et al, 2013;Subke et al, 2012;Tavi et al, 2013;Weng et al, 2017). The fate of this C is ultimately controlled by the composition and activity of soil biota, however our understanding of the below ground C flux and its partitioning amongst roots, mycorrhizae and free living soil microbes is still limited (De Deyn et al, 2008;Stuart Chapin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Cover crops provide additional biomass inputs from above-and belowground (Blanco-Canqui, Mikha, Presley, & Claassen, 2011), increase carbon and nitrogen inputs, and enhance the biodiversity of agroecosystems (Lal, 2004). Biochar amendments affect SOC dynamics through two pathways: (a) improving soil aggregation and physical protection of aggregate-associated SOC against microbial attack; and (b) increasing the pool of recalcitrant organic substrates resulting in a low SOC decomposition rate and substantial negative priming (Du, Zhao, Wang, & Zhang, 2017;Weng et al, 2017;Zhang et al, 2012). Biochar amendments affect SOC dynamics through two pathways: (a) improving soil aggregation and physical protection of aggregate-associated SOC against microbial attack; and (b) increasing the pool of recalcitrant organic substrates resulting in a low SOC decomposition rate and substantial negative priming (Du, Zhao, Wang, & Zhang, 2017;Weng et al, 2017;Zhang et al, 2012).…”
mentioning
confidence: 99%